Primary pulmonary myoepithelial carcinoma in a young woman: A case report and review of literature. Issue 9 (March 2018) - Zhou, Xiaojuan; Yu, Min; Zhuo, Hongyu; Zhang, Shuang
Abstract: Rationale: Myoepithelial carcinoma mainly occurs in the salivary glands, but myoepithelial carcinoma of the lung is extremely rare neoplasm whose biological behavior and clinical course still remain to be fully elucidated. Although considered as low-grade carcinoma, these tumors have a high rate of recurrence or distant metastasis. Patient concerns: To date there are only 11 cases of pulmonary myoepithelial carcinoma reported in the English literature. We report a case of a 24-year-old woman diagnosed with primary pulmonary myoepithelial carcinoma. Informed consent was obtained from the patient. Diagnoses: The tumor derived from superior lobe of left lung and exhibited only myoepithelial differentiation without any ductal formation by histopathological and immunohistochemical analysis. Interventions: The patient underwent the left superior lobe resection. In addition, we first introduce second-generation sequencing technology as a novel strategy for primary pulmonary myoepithelial carcinoma, and these tumors should be included in the differential diagnosis of thoracic neoplasms. Outcomes: The patient was alive with no evidence of disease for up to 12 months. Lessons: Individualized treatment is the promising clinical strategy for thoracic neoplasms, and the underlying molecular events should be investigated to find the potential therapeutic targets.